Arquitetura e neurociência: o projeto paisagístico como auxílio ao tratamento não farmacológico da doença de Alzheimer - FARIA, Barbara Alves Cardoso de (2018)
This research has the purpose to study how the landscape design in clinics that attend patients with Alzheimer's disease can contribute to the non-pharmacological treatment of the disease and improve the patient's quality of life. Studies related to the brain indicate that the built environment has the potential to interfere directly in the brain structure. Thus, neuroscience can contribute to the planning and analysis of constructed spaces with the purpose of offering suitable conditions for the well-being of the individual with this pathology. Regarding constructed spaces, the landscaping project acts as a relevant element in clinics that attend patients with Alzheimer's disease. The patient's relationship with nature is essential because being around green areas provides effects such as alignment of his circadian rhythm, increased vitamin D production, basic notions of time, air quality and sensory stimuli. Thus, the landscaping and architectural elements of green areas can serve as cognitive stimuli to the brain, reestablishing the contact of the human being with the surrounding environment. In this way, such stimuli have the capacity to promote a condition of well-being, providing comfort, security and helping in the healthy living of these individuals in the built space. From this, the research analyzes the design of green areas of two Alzheimer's care clinics, with the purpose of evaluating and recognizing the importance of such areas, as well as offering discussions and recommendations to the landscaping project of both clinics. For this, a bibliographical survey was carried out of authors that relate neuroscience and architecture, as well as field research, both essential to propose a series of recommendations with the purpose of suggesting guidelines and improvements for green areas of such clinics. This study demonstrates the relevance of a landscape design for spaces that shelter patients with diseases that affect the central nervous system, such as Alzheimer's.